2016
DOI: 10.18632/oncotarget.14044
|View full text |Cite
|
Sign up to set email alerts
|

PRKAR2B plays an oncogenic role in the castration-resistant prostate cancer

Abstract: Castration-resistant prostate cancer (CRPC) is an advanced form of prostate cancer. Despite some progresses have been made, the mechanism of CRPC development is still largely unknown, including the genes involved in its development have not been well defined. Here, we identifiedPRKAR2B to be a gene over-expressingin castration-resistant prostate cancer by analyzing the different online databases. Followed functional validation experiments showed that PRKAR2B promoted CRPC cell proliferation and invasion, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 34 publications
(40 reference statements)
2
30
0
Order By: Relevance
“…Results shown are the mean of two independent experiments AE SD (100 cells/experiment, *P < 0.5, **P < 0.01, ***P < 0.001, ns: not significant t-test). proteins Ran1Gap2 and Prkar2B were perturbed in the global proteome ( Fig 8B-D) [34,[58][59][60]. Consistent with the proteomics data, a significant increase in the cellular abundance of Cep131 and a significant decrease in SLAIN2 was detected using immunoblotting experiments ( Fig 4G).…”
Section: Loss Of Satellites Leads To a Rearrangement Of The Global Prsupporting
confidence: 83%
“…Results shown are the mean of two independent experiments AE SD (100 cells/experiment, *P < 0.5, **P < 0.01, ***P < 0.001, ns: not significant t-test). proteins Ran1Gap2 and Prkar2B were perturbed in the global proteome ( Fig 8B-D) [34,[58][59][60]. Consistent with the proteomics data, a significant increase in the cellular abundance of Cep131 and a significant decrease in SLAIN2 was detected using immunoblotting experiments ( Fig 4G).…”
Section: Loss Of Satellites Leads To a Rearrangement Of The Global Prsupporting
confidence: 83%
“…Protein kinase cAMP‐dependent regulatory type II beta (PRKAR2B) plays a role in oocyte maturation, 8 regulates murine and human adipocyte differentiation 9 and inhibits the effect of cAMP responsive element binding protein (CREB) activity in T cells 10 . Recently, we identified PRKAR2B as a novel oncogene implicated in the development of CRPC 11,12 . Moreover, PRKAR2B induces the epithelial‐mesenchymal transition process and promotes prostate cancer metastasis by activating Wnt/β‐catenin signalling pathway 13 …”
Section: Introductionmentioning
confidence: 99%
“…Included in the PKA family is cAMP-dependent type 2 regulatory subunit beta ( Prkar2b ), a form of RIIβ; these genes are primarily expressed in brain tissue, brown adipose tissue, and white adipose tissue [7, 8]. Prkar2b has the ability to regulate leukemia cell differentiation [9], plays a role in motoneurons [10] and alternative signaling of cAMP pathways [11], suppresses the effect of cAMP responsive element binding protein (CREB) activity in T cells [12], regulates adipocyte differentiation [13], and plays an oncogenic role in prostate cancer [14]. A recent study found that Prkar2b -deficient mice experience a decrease in white adipose tissue and an increase in resting metabolic activity, body temperature, and lipid hydrolysis [7].…”
Section: Introductionmentioning
confidence: 99%